Technique for Measuring the Internal Diameter and Area of Visible Vessels of the Eye - V. A. Firago; A. I. Kubarko (Приборы и методы измерений)
The study of the effects on the microvasculature of various vasoactive drugs requires appro-priate methods and equipment for determining the basic physiological parameters of small blood vessels: their internal diameter and cross-sectional area, specific density, and blood flow velocity. Therefore, the purpose of the article is to study the possibilities of improving the reliability of determining the internal diameter and cross-sectional area of the visible blood vessels of bulbar con-junctival of the eye.A technique for obtaining digital video recordings of the bulbar conjunctiva of the eye, based on the pulse illumination of the study area, is proposed. A prototype of the equipment with a spatial resolution of 2 µm video is described, which allows to trace all visible blood vessels, including capillaries. An algorithm for stabilizing the position of a sequence of digital images of the bulbar conjunctiva relative to the first frame is discussed. It is based on the use of subpixel interpolation when searching for a global minimum of the standard deviation of the differences in brightness of the first and selected frame.The proposed algorithms for tracing the vascular pattern and determining the internal diameter and cross-sectional area of the blood vessels are described. An original method for calculating them is proposed, which is based on determining the area and height of a cross section of a blood vessel image. The problem of verification of the obtained results is discussed.The described approach to make it possible to create diagnostic images of the visible blood vessels of the bulbar conjunctiva, including the capillaries, with an indication of their diameters. Examples of the construction of histograms of the distribution of the internal diameter and cross-sectional area of these blood vessels are presented.The proposed technique and hardware solutions have the prospect of being used in creating equipment for complex non-invasive diagnostics of the microvasculature and monitoring the effectiveness of treating various diseases of the cardiovascular system, since the conditions of the eye blood vessels correlate with the state of the blood vessels in other organs.